Increased private health fund involvement in Australia's primary health care: Implications for health equity. Issue 4 (1st August 2018) - Windle, Alice; Fisher, Matthew; Freeman, Toby; Baum, Fran; Javanparast, Sara; Kay, Adrian; Kidd, Michael
Abstract: This study identifies current practices of private health funds (PHFs) in Australian primary health care (PHC), including areas where their involvement is increasing, and examines the risks and benefits of these practices for quality of, and equity of access to PHC. The paper draws on research to investigate equity implications of current PHF involvement in PHC in Australia. We reviewed literature, analysed documents relating to a Senate Committee inquiry and interviewed stakeholders and experts in private health insurance policy from government, private sector and nongovernment organisations. Involvement of PHFs in the PHC sector in Australia is increasing, presenting risk of increased inequities in access to PHC based on insurance status, which could undermine the universality of PHC under Medicare. However, some stakeholders think these risks can be managed within current policy arrangements. There are also risks for quality of PHC services arising from greater involvement of PHFs in service delivery and "preferred provider" models. Differing stakeholder views on equity implications of PHF involvement in PHC are associated with different views on desirable policy action. We conclude that there is a risk of increased involvement of PHFs in PHC risks exacerbating existing inequities in the health system, but this is moderated by public support for Medicare.